Lapsansky, E. J. and Verplanck, A. A. "Quaker Aesthetics: Reflections on a Quaker Ethic on American Design and Consumption" - Homan, Roger (Quaker studies, 2004)
Lapsansky, E. J. and Verplanck, A. A. (eds), Quaker Aesthetics: Reflections on a Quaker Ethic on American Design and Consumption, Philadelphia: University of Pennsylvania Press, 2003. pp. xiv + 394, ISBN 0-8122-3692-0, Cloth, £24.50,$ 35